Heritage Dynamics Understanding and adapting to change in diverse heritage contexts - Fouseki, Kalliopi (UCL Press, 2022)
How does heritage emerge, change, stagnate, disappear and/or revive over time? Should heritage be approached as a 'non-renewable resource' that needs to be sustained for eternity, or as a 'renewable resource' that adapts to change and transformation? Heritage Dynamics deconstructs the dynamic nature of heritage. Heritage as a socio-cultural practice goes through non-linear, continuous lifecycles, where certain factors will be the catalyst for the ending of one lifecycle and the revival for another. Kalliopi Fouseki develops a theoretical and methodological framework of 'heritage dynamics', which is used as the analytical thread of six heritage contexts: heritage-led transformation in historic urban places; decision-making on energy efficiency and heritage conservation in 'everyday heritage' residential buildings; lifecycles of heritage collections; exhibition dynamics and the impact of participation with emphasis of 'difficult heritage'; dynamics of dissonance on contested museums and the dynamics of 'intangible heritage' with emphasis on flamenco. The book offers a new theoretical and methodological framework that will enable heritage scholars and practitioners to unpack the ways and conditions under which heritage changes. The new theoretical framework will re-orientate current thinking of heritage as a thing, a process or discourse towards a new, more systemic thinking that captures the complexity of heritage. Methodologically, Heritage Dynamics introduces the potential of systemic methods, such as system dynamics, in capturing the dynamic nature of heritage. The new theory and method not only opens up new avenues for theoretical explorations, but also offers a significant tool for heritage managers and policymakers.